Moderate Behavior of Prophet Muhammad (PBUH) as a Role Model in Encountering Pluralism - Ahmad Riyadh Maulidi (Universitas Islam Negeri (UIN) Walisongo Semarang, Indonesia, 2021)
Moderation is the attitude of being in the middle that must be owned by a Muslim, especially Muslims in Indonesia who live amid pluralism. Problems in Indonesia related to intolerant behavior are mainly caused by the lack of moderate attitudes, especially Muslims. Islam should be a pioneer in implementing this reasonable behavior as the majority religion. The research describes some moderate behaviors exemplified by the Prophet Muhammad (SAW) during his life as a role model for Muslims. This research is qualitative descriptive research with a literature study method. The results showed that the moderate behavior of the Prophet Muhammad was reflected in his behavior when Surah al-Kafirun was revealed, his tolerance towards other religions, and his wisdom in solving the problem of laying the Black Stone. He is moderate in doing worship, not excessive. He also sleeps, breaks his fast, gets married, and orders people to pray in a new state that the values of moderate behavior from the exemplary human figure of the Prophet Muhammad (SAW) can be applied in overcoming the challenges of a pluralistic life to create a sense of unity.